Penerapan Pola Hidup Sehat untuk Mencegah Diabetes Mellitus - Karmana, I Wayan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Obesity is overweight due to excessive accumulation of fat in the body. Fat accumulation occurs when food intake exceeds the energy expended in activity. The obesity rate continues to increase every year, with the number of adult males increasing from 13.9% in 2007 to 19.7% in 2013. As for adult women, there is a very extreme increase of 18.9%, from 1 to 14 .8% in 2007 to 32.9% in 2013. The purpose of this study is to help provide knowledge about the importance of a healthy lifestyle and the dangers of diabetes mellitus. The research method in this article uses case studies (Library Research) with writing techniques to collect data and information from books and related journal references. The result of writing this article is that there are still many people with diabetes mellitus who do not understand the disease, as well as the lack of early education for all who are not familiar with diabetes mellitus.